Digital Cell Atlas of Mouse Uterus: From Regenerative Stage to Maturational Stage - Zhang, Leyi; Long, Wenying; Xu, Wanwan; Chen, Xiuying; Zhao, Xiaofeng; Wu, Bingbing (Frontiers in Genetics, 2022)
Endometrium undergoes repeated repair and regeneration during the menstrual cycle. Previous attempts using gene expression data to define the menstrual cycle failed to come to an agreement. Here we used single-cell RNA sequencing data of C57BL/6J mice uteri to construct a novel integrated cell atlas of mice uteri from the regenerative endometrium to the maturational endometrium at the single-cell level, providing a more accurate cytological-based elucidation for the changes that occurred in the endometrium during the estrus cycle. Based on the expression levels of proliferating cell nuclear antigen, differentially expressed genes, and gene ontology terms, we delineated in detail the transitions of epithelial cells, stromal cells, and immune cells that happened during the estrus cycle. The transcription factors that shaped the differentiation of the mononuclear phagocyte system had been proposed, being Mafb, Irf7, and Nr4a1. The amounts and functions of immune cells varied sharply in two stages, especially NK cells and macrophages. We also found putative uterus tissue-resident macrophages and identified potential endometrial mesenchymal stem cells (high expression of Cd34, Pdgfrb, Aldh1a2) in vivo. The cell atlas of mice uteri presented here would improve our understanding of the transitions that occurred in the endometrium from the regenerative endometrium to the maturational endometrium. With the assistance of a normal cell atlas as a reference, we may identify morphologically unaffected abnormalities in future clinical practice. Cautions would be needed when adopting our conclusions, for the limited number of mice that participated in this study may affect the strength of our conclusions.